1933
DOI: 10.1055/s-0028-1131656
|View full text |Cite
|
Sign up to set email alerts
|

Neue Fälle der Pelgerschen familiären Kernanomalie der Leukozyten1

Abstract: Infolge eines günstigen Zusammentreffens liefen bei Verfasser in letzter Zeit von den verschiedensten Seiten Präparate zusammen, die einer der merkwürdigsten Entdeckungen auf dem Gebiete der Blutlehre, einer konstitutionellen Kernanomalie der Leukozyten, Bestätigung, Erweiterung und neue Gesichtspunkte zubrachten. Es handelt sich um die, von dem holländischen Hämatologen Dr. P,nem, Amsterdam, entdeckte eigenartige Form schwerer Kernverschiebung der 1 Demonstration im Verein für Innere Medizin am 9. I. 1933.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1934
1934
1974
1974

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In 1931 he reported a second case, and Huet (1931) found similar cells in a niece of one of Pelger's patients which led to the examination of the remaining relatives and the finding of other affected members, whom Huet reported with two more families from Holland in 1932. In the same year the publications of Burger and J ordans appeared, and in 1933 Undritz described a family from Switzerland with what he then called the pseudo-regenerative white blood cell picture, and Schilling (1933) fully investigated two new families, one from Czechoslovakia and one from Germany (Weigeldt, 1933) . It was Schilling who first suggested that the unusual change in the white cells be termed the Pelger-Huet anomaly of the leucocytes.…”
Section: Review Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…In 1931 he reported a second case, and Huet (1931) found similar cells in a niece of one of Pelger's patients which led to the examination of the remaining relatives and the finding of other affected members, whom Huet reported with two more families from Holland in 1932. In the same year the publications of Burger and J ordans appeared, and in 1933 Undritz described a family from Switzerland with what he then called the pseudo-regenerative white blood cell picture, and Schilling (1933) fully investigated two new families, one from Czechoslovakia and one from Germany (Weigeldt, 1933) . It was Schilling who first suggested that the unusual change in the white cells be termed the Pelger-Huet anomaly of the leucocytes.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…The blood groups are not given. Schilling (1933) was the first to point out the possible medico-legal importance of the anomaly, and Undritz (1943) conjectured that as all the leucocytes are affected in this condition, the general body cells may be affected also, at least those which develop from the mesenchyme.…”
Section: Blood Counts Of the Affected Membersmentioning
confidence: 99%